Quality Analysis of Management Accounting Information Systems and Organizational Structures on Management Decision Making - Dewi Kania Puspita Resmi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
Management decision making is expected to provide great benefits in the business world. Management of a company requires a variety of fast information and accuracy needed for various management decisions. Without the support of relevant data and information, the management's decisions at various levels of the organization can be wrong and not according to needs. Phenomena in the field regarding management in decision making do not think about problems that will occur in the future that can harm the company and management to make decisions unilaterally based on the input of information received that is not yet relevant. This study aims to determine the effect of the quality of management accounting information systems and organizational structure on management decision-making. The method used in this study is a descriptive method with a quantitative approach through data collection techniques with questionnaires that are distributed directly throughout the section heads in PT. Macrosentra Niagaboga. The statistical test instrument used in this study is the Sructural Equation Model (SEM) with Partial Least Square (PLS) assessment. Application of quality management accounting information systems, organizational structure, and management decision making at PT. Macrosentra Niagaboga is in good criteria. The results of this study show 1) There is a significant influence on the quality of management accounting information systems on management decision making. 2) organizational structure has a significant influence on management decision making.